Responses of peripheral endocannabinoids and endocannabinoid-related compounds to hedonic eating in obesity - Monteleone, A M; Di Marzo, V; Monteleone, P; Dalle Grave, R; Aveta, T; Ghoch, M El; Piscitelli, F; Volpe, U; Calugi, S; Maj, M (European journal of nutrition, 2016)
Purpose Hedonic eating occurs independently from homeostatic needs prompting the ingestion of pleasurable foods that are typically rich in fat, sugar and/or salt content. In normal weight healthy subjects, we found that before hedonic eating, plasma levels of 2-arachidonoylglycerol (2-AG) were higher than before nonhedonic eating, and although they progressively decreased after food ingestion in both eating conditions, they were significantly higher in hedonic eating. Plasma levels of anandamide (AEA), oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), instead, progressively decreased in both eating conditions without significant differences. In this study, we investigated the responses of AEA, 2-AG, OEA and PEA to hedonic eating in obese individuals. Methods Peripheral levels of AEA, 2-AG, OEA and PEA were measured in 14 obese patients after eating favourite (hedonic eating) and non-favourite (nonhedonic eating) foods in conditions of no homeostatic needs. Results Plasma levels of 2-AG increased after eating the favourite food, whereas they decreased after eating the non-favourite food, with the production of the endocannabinoid being significantly enhanced in hedonic eating. Plasma levels of AEA decreased progressively in nonhedonic eating, whereas they showed a decrease after the exposure to the favourite food followed by a return to baseline values after eating it. No significant differences emerged in plasma OEA and PEA responses to favourite and non-favourite food. Conclusion Present findings compared with those obtained in our previously studied normal weight healthy subjects suggest deranged responses of endocannabinoids to food-related reward in obesity.